Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kepuasan Kerja dan Kinerja Karyawan pada Karma Jimbaran - Yasa, I Putu Sedhana; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2014)
Employee performance has a major contribution in the achievement of corporate goals. High performance is influenced by employee satisfaction in terms of receiving compensation and satisfaction with the work environment. This study aims to determine the effect of compensation and work environment on job satisfaction and performance. The study was conducted at the Karma Jimbaran by involving all employees. Data sourced research of primary and secondary data were collected through interviews and distribution of questionnaires. The data analysis technique used in this study is the technique of path analysis. The results showed that a positive and significant direct job satisfaction and performance is affected by the compensation and work environment. Keywords: compensation, work environment, job satisfaction and performance